Factors influencing procalcitonin in the cerebrospinal fluid of patients after neurosurgery and its diagnostic value for intracranial infection - Huajun Wang; Chengjie Zhou; Ye Fu (BMC Neurology, 2023)
Abstract Objective This study aimed to investigate the factors influencing Procalcitonin (PCT) in the cerebrospinal fluid (CSF) of patients with high fever and suspected intracranial infection after neurosurgery and its clinical application value. Methods Between February 2021 and August 2022, CSF and serum samples were collected via lumbar puncture from patients with high fever and suspected intracranial infection in the Intensive Care Unit(ICU) of our hospital. Multivariate logistic regression analysis was performed to analyze the factors influencing elevated PCT in CSF. The diagnostic efficacy of each index was assessed using receiver operating characteristic (ROC) curves. Results A total of 183 CSF samples were collected, of which 148 had increased PCT levels, including 73 cases of intracranial infection and 75 cases in the case‒control group. Multivariate logistic regression analysis showed that intracranial infection [OR = 0.117, 95% CI: 0.025–0.559; p < 0.01] and hemorrhagic CSF [OR = 0.162, 95% CI: 0.029–0.916; p < 0.04] were factors influencing CSF PCT, while trauma [OR = 3.43, 95% CI: 0.76–15.45; p < 0.12], epileptic seizure [OR = 0.00, 95% CI: 0.00; p < 0], age [OR = 1.02, 95% CI: 0.98–1.52; p < 0.32] and Glasgow Coma Scale (GCS) score [OR = 1.03, 95% CI: 0.78–1.32; p < 0.83] did not influence CSF PCT. The CSF PCT and serum PCT levels in the intracranial infection group and the case‒control group were 0.13 (0.11, 0.25) ng/ml and 0.14 (0.07, 0.25) ng/ml and 0.14 (0.08,0.32) ng/ml and 0.23 (0.13,0.48)ng/ml, respectively, with no statistically significant difference. The median values of CSF lactate in the intracranial infection group and the case‒control group were 6.45 (4.475, 8.325) mmol/l and 3.2 (2.02, 4.200) mmol/l, respectively, with a statistically significant difference between the groups.The areas under the ROC curve of CSF PCT, serum PCT,CSF lactate, CSF PCT combined with lactate were 0.59, 0.63, 0.82,and 0.83,respectively. Conclusion Intracranial infection and hemorrhagic CSF are influencing factors for elevated CSF PCT following neurosurgery. It should be noted that the diagnostic value of intracranial infection by CSF PCT elevated alone is limited, but the combination it with other indicators can help improve diagnostic efficacy.